The Importance of Reducing Overbite Before Overjet with Initial Treatment Mechanics - Jenner John D. (Sciendo, 1995)
Rapid overjet reduction commonly experienced with the rihbon arch bracket may inadvertently have a major influence on prorile control. The main purpose of this paper is to warn of the danger of early upper incisor retraction, particularly in the deep bite patient in whom the upper incisor retraction itself is the direct cause of the backward mandibular rotation. The paper explores the incisor interference phenomenon as a major cause of backward mandibular rotations and suggests means of avoiding incisor interference by moddification of the treatment plan and treatment mechanics.